COMMUNITY VULNERABILITY TO FLOOD DISASTER PROBLEMS - Firstika Nabilla B; Bunga Elvyan Br Damanik; Latifah Mutiah Nurhidayah; Intan Kusumawati; Sandiyatun Daulay; Putra Apriadi Siregar (Lembaga Pengembangan Kinerja Dosen, 2023)
Flood is an event of flow or stagnation of water in an area that occurs due to the overflow of water from existing canals exceeding the capacity of water disposal caused by high rainfall and the topographical conditions of the area in the form of lowlands to basins, causing physical, social and economic losses. This type of research is qualitative research because the results of this research were obtained from various data collection techniques such as interviews, document analysis, observation and documentation. The population in this study were residents in Tanjung Rejo Village, Medan Sunggal District. The sample is part of the population that has a quality that can represent the entire population. The sampling process was carried out non-randomly (nonprobability sampling) with a purposive sampling technique, namely the method of taking samples based on certain withdrawals. The criteria referred to in this study are local residents who have been affected by floods.